The Impact of Homosexuality on Islamic Belief, Values, and Cultures - Tanimu, Baba (Jurnal Usuluddin, 2025)
Homosexuality is one of the most common illicit types of sexualities produced by modernity. Most people must be familiar with terms such as homosexual, transsexual, and bisexual, but these are not the only sexual orientations that are produced by modernity in this world. There are as many as sixteen types that exist in the world. However, insufficient discourse and attention have been given by the government, social actors, and Islamic scholars in identifying the menace, and its escalation is worrisome. Therefore, this article examines the impact of homosexuality on Islamic beliefs, values, and culture, employing a qualitative method that combines historical, documentary, and analytical approaches. The findings reveal that homosexuality as a product of modernity has an impact on the Islamic belief systems, social values of Islam, and cultures. The article further systematically pin pointed the strategies deployed by the modernists in inculcating these notorious and illicit acts in the minds of the Muslim youth in the disguise of colonialism, neo-colonialism, and secularism. This article, therefore, recommends that the marriage institution should be preserved from the Islamic perspective for the obliteration of these illicit modern sexualities, with a particular focus on homosexuality.